2002
DOI: 10.1074/jbc.m202959200
|View full text |Cite
|
Sign up to set email alerts
|

Interferons Inhibit Tumor Necrosis Factor-α-mediated Matrix Metalloproteinase-9 Activation via Interferon Regulatory Factor-1 Binding Competition with NF-κB

Abstract: Invasion and metastasis of tumor cells is a multiple process, in which cell motility is accompanied by uncontrolled degradation of basement membrane and components of the extracellular matrix (1, 2). Matrix metalloproteinases (MMPs) 1 are a family of related zinc-containing proteinases that have the ability to degrade most extracellular matrix (3, 4). One member of the MMP family, MMP-9 (gelatinase B, 92-kDa), contains fibronectin-like domains for collagen binding and is capable of degrading type I, IV, V, V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 49 publications
(82 reference statements)
5
78
1
Order By: Relevance
“…Similar data are available for MMPs (26,27), whose control by genetic (29) and pharmacological means (30) has been shown to inhibit the aggressiveness of experimental melanoma. However, information on the control of these proteases by inflammatory cytokines in tumor cells is still limited, and an inconsistency in the trend is seen in the present information (31)(32)(33)(34)(35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 56%
“…Similar data are available for MMPs (26,27), whose control by genetic (29) and pharmacological means (30) has been shown to inhibit the aggressiveness of experimental melanoma. However, information on the control of these proteases by inflammatory cytokines in tumor cells is still limited, and an inconsistency in the trend is seen in the present information (31)(32)(33)(34)(35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 56%
“…The cDNAs for human b 2 -microglobulin, ACE and TACE were amplified by PCR, and primers were designed according to published sequences (Costerousse et al, 1993;Satoh et al, 2000;Sanceau et al, 2002). b 2 -Microglobulin cDNA (165 bp) was amplified using the sense primer 5 0 -CAT CCA GCG TAC TCC AAA GA-3 0 and the antisense primer 5 0 -GAC AAG TCT GAA TGC TCC AC-3 0 .…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…Following cell stimulation with IFNg (1000 U/ml) for 16 h, total cell extracts were prepared, separated on 12% polyacrylamide-sodium dodecyl sulphate gels, transferred to nitrocellulose and blotted as described (Sanceau et al, 2002). Membranes were hybridized with Abs for IRF1 and actin as described (Sanceau et al, 2002) using chemiluminescence technique developed by Santa Cruz.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanisms are not clear, it has been reported that IFNs inhibit TNF-a-mediated MMP-9 activation via IFN regulatory factor-1 binding competition with NF-jB. 39 Therefore, TL -pulsed DCs induce CTL in cancer tissues, which produce IFNs, inhibit MMP-9 activation and may lead to apoptosis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%